Analisa Drum Penampung Air Ketel Dengan Kapasitas Uap 43 Ton/jam dan Tekanan 28 kg/cm2 pada Pabrik Pengolahan CPO (Crude Palm Oil) - Lelawati Lelawati (MAJALAH TEKNIK SIMES, 2022)
Abstract Palm oil processing plants (CPO) in the process really need the role of a steam boiler. A steam boiler is a device that works by heating water to a boil and producing steam. A steam boiler basically consists of a drum that is closed on both sides, with a to hold water. The classification of the steam boiler can be based on the fluid flowing in the pipe, its use, the location of the kitchen, the location of the pipe, the water circulation system, and the boiler heat source. This water in the drum is not only used to get steam heating, it is also useful to prevent the temperature rise that is too high from the parts that are directly related to the flue gas. Theoretically, to get steam with a capacity of 43 tons/hour and a pressure of 28 kg/cm2, the area of the drum pipe A = 28.26 m², the thickness of the drum plate T = 0.875 cm, the stress that arises in the transverse direction = 1184.05 kg /cm² In planning the allowable stress is 2400 kg/cm², and the calculation results are 1184.05 kg/cm². So this plan meets the requirements that t is 2400 kg/cm² 1184.05 kg/cm². Inspection that the drum does not break 0.875cm 0.4 Meets the requirements that the drum is not easily broken